Family Caregiver Burden of Elderly with Dementia: A Literature Review - Biran, Rakhel Maharani Putri Yusyah; Setyawati, Martyarini Budi; Siwi, Adiratna Sekar (Jurnal Berita Ilmu Keperawatan, 2022)
The majority of the elderly with dementia living in a community have received care from family caregivers with curious complexity of problems to be identified during the care at home. Caregiver burden conceptualized as multidimensional concept encompassing the emotional, physical, and socioeconomic aspects of the impact of caregiving role. This study aims to review articles and journals about the level of burden and characteristics that have an impact on the burden of elderly caregivers with dementia. A literature review with a search for relevant articles was published between 2015-2020 using databases PubMed, Google Scholar, DOAJ, and Oxford Academic Journals. Keywords used to retrieve literature include caregiver burden and dementia. The results is nineteen articles that met the inclusion criteria and were identified in this literature review. Most family caregivers were identified as having a moderate level of caregiving burden that depends on various factors including characteristics of elderly with dementia, sociodemographic characteristics of caregivers, and characteristics of care itself. The conclussion of this, mostly caregivers reported in this review were more likely to experience a moderate level of caregiving burden with the presence of behavior problems, neuropsychiatric symptoms